Understanding of Adventitious Root Formation: What Can We Learn From Comparative Genetics? - Mhimdi, Mariem; Pérez-Pérez, José Manuel (Frontiers in Plant Science, 2020)
Adventitious root (AR) formation is a complex developmental process controlled by a plethora of endogenous and environmental factors. Based on fossil record and genomic phylogeny, AR formation might be considered as the default state of plant roots, which likely evolved independently several times. The application of next-generation sequencing techniques and bioinformatics analyses to non-model plants provide novel approaches to identify genes putatively involved in AR formation. Recent results have shown that the regulation of shoot-borne AR formation in monocots is an adaptive response to nutrient and water deficiency and that enhances topsoil foraging to improve plant performance. A hierarchy of transcription factors required for AR initiation has been identified from genetic studies, and recent results highlighted the key involvement of additional regulation through microRNAs. Here we discuss our current understanding of AR formation in response to specific environmental stresses, such as nutrient deficiency, drought or waterlogging, aimed at providing evidence for the integration of the hormone crosstalk required for the activation of root competent cells within adult tissues from which the ARs will develop.